Microbiome baseline for an Arctic sentinel: spatial patterning of nasal and anal microbiomes in ringed seals - Carlos A. Domínguez-Sánchez; Olwyn C. Friesen; Brent G. Young; Tera L. Edkins; Ellen V. Lea; Magali Houde; Stephen D. Petersen; David J. Yurkowski; Holly E. L. Gamblin; Steve H. Ferguson (Frontiers in Marine Science, 2026)
Introduction Ringed seals ( Pusa hispida ) are sentinel species of Arctic change, yet baseline microbiome data across their circumpolar range remain limited. Methods We profiled nasal and anal microbiomes from 90 free-ranging ringed seals across eight Arctic and sub-Arctic locations in Canada using 16S rRNA gene amplicon sequencing. Results Body site was the primary determinant of microbiome structure, with nasal and anal assemblages forming distinct communities that could be classified with 94.8% accuracy, consistent with strong niche partitioning. Nasal microbiomes exhibited a conserved core dominated by the genera Corynebacterium, Psychrobacter , and Suttonella across all sampling locations, supporting a stable respiratory baseline consistent with host-mediated filtering. In contrast, anal microbiomes showed higher richness, greater inter-individual variability, and a latitudinal gradient in diversity: Shannon index, Pielou’s evenness, and Simpson index all declined with increasing latitude (all p < 0.05), suggesting that ecological constraints at higher latitudes promote dominance by a narrower set of taxa without reducing overall richness. Despite overall compositional differences among locations, geographic distance was a poor predictor of microbiome dissimilarity in both body sites. Instead, continuous spatial gradients of latitude and longitude were associated with microbiome composition in both body sites: in nasal microbiomes, genus Corynebacterium increased while Ornithobacterium and Suttonella decreased at higher latitudes, whereas in anal microbiomes, Psychrobacter and Peptoclostridium increased northward while Fusobacterium and Bacteroides declined, patterns not previously reported in Arctic pinnipeds. Conclusion Together, these findings establish the first integrated nasal and anal microbiome baseline for ringed seals, demonstrate that the two body sites provide complementary ecological signals, and establish a reference framework for future microbiome-based health monitoring in a rapidly changing Arctic.